A Note on Pensions and Firm Performance: First Evidence from German Micro Data - Schnabel, Claus; Wagner, Joachim (Journal of Labor Research, 2001)
Using a large new data set we present results from the first econometric study of the effects of pensions on firm performance in Germany. We find evidence for positive effects on wages, reduction of labor turnover, training, and profit
UnivIS-Import:2015-03-09:Pub.2001.rw.fbwiwi.LVS.anoteo
Keywords: Labor productivity; Firm performance; Pension Plan; Public Pension; Econometric Study